Maturidade da cultura de segurança no trabalho: aplicação do modelo de hudson - Grandinete, Isabella C.; Sousa, Tatiane G. de; Brandstetter, Maria Carolina G. O. (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
This study aims to contribute to an improvement in the management of workers health and safety. Through a bibliographical review the work brings several concepts about safety culture at work, showing that there is still a consensus among the scholars about the subject and showing the importance of understanding the same for organizations success. It sought to analyze the maturity degree of work safety culture in a construction company in Goiânia, through application of a questionnaire based on Hudson’s model. The model is an important managerial tool, because it can define in which of the five stages (pathological, reactive, bureaucratic, proactive and sustainable) the company finds itself, through the way it treats the following factors: information, organizational learning, involvement, communication and commitment. The result of this research demonstrated that both the workers and the administrative team attribute to the organization a transition between the proactive and sustainable stage, but most of it is allocated in the sustainable stage, considered the ideal stage. Safety culture is of paramount importance for improving the well-being of workers towards the work environment, as it contributes to reduction of risks and accidents, requiring a greater investment in this area, either through new studies and research or by the entrepreneurs' awareness.